Materializing and Performing: Jōkei's Mañjuśrī Faith and the Kasagidera Restoration - Quinter, David (Japanese journal of religious studies, 2016)
This article illuminates the significance of the Mañjuśrī cult during Jōkei's (1155-1213) Kasagi years and his innovative synthesis of material, textual, and ritual culture. The study of such medieval Nara scholar-monks as Jōkei suffers from lingering biases that privilege the Buddhist schools strongest now over the many other movements thriving in medieval Japan. Their activities are typically cast as reactionary responses to popularizing tendencies championed elsewhere rather than as creative transformations of Buddhist teachings and practices in their own right. Even amid revisionist studies, the textual concerns of scholar-monks are often contrasted with the “lived religion” in such practices as icon veneration, pilgrimage, and simplified chanting rituals. However, this article uses Jōkei's involvement in the Kasagidera restoration and the Mañjuśrī cult, including his composition of a kōshiki devoted to Mañjuśrī (Jp. Monju), to show how these same practices were integral to the concerns of Nara scholar-monks. The online supplement includes a complete annotated translation of Jōkei's Monju kōshiki.